2022
DOI: 10.3390/molecules27175460
|View full text |Cite
|
Sign up to set email alerts
|

Myrcia paivae O.Berg (Myrtaceae) Essential Oil, First Study of the Chemical Composition and Antioxidant Potential

Abstract: The Myrtaceae family is one of the most representative in the Amazon. Several species have high added-value pharmacological potential. In order to contribute to the knowledge of the aromatic profile of Myrtaceae species from the Amazon, the present study presents the first report on the productivity, chemical composition, and antioxidant profile of the essential oil (EO) of Myrcia paivae. Dry leaves of the species were submitted to hydrodistillation to obtain their EO. The EO performance was calculated on a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The extraction of PCEO via hydrodistillation provided a higher yield of essential oil (7.33% v/w) when compared to reports of other species of the same family, such as Myrciaria tenella, Calycorectes sellowianus [35], and Myrcia paivae [36]. The chemical characterization of crude essential oils has a pivotal role in identifying the major components and understanding their possible mechanism of action.…”
Section: Resultsmentioning
confidence: 98%
“…The extraction of PCEO via hydrodistillation provided a higher yield of essential oil (7.33% v/w) when compared to reports of other species of the same family, such as Myrciaria tenella, Calycorectes sellowianus [35], and Myrcia paivae [36]. The chemical characterization of crude essential oils has a pivotal role in identifying the major components and understanding their possible mechanism of action.…”
Section: Resultsmentioning
confidence: 98%
“…Monoterpenes are natural organic compounds that represent a large group in the field of chemistry [ 38 ]. In this study, it was possible to observe that this chemical class characterized the profile of the essential oils of Myrcia lundiana (MLUN19), M. lundiana (MLUN23), M. mollis , M. ovata , and M. Paivae [ 7 , 13 , 39 , 40 ].…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…De Moraes et al [ 7 ] reported the antioxidant activity of Myrcia floribunda and Myrcia sylvatica essential oil via ABTS •+ and DPPH • methods. The results of their study indicated that the essential oil (EO) of M. floribunda exhibited an ABTS •+ inhibition rate of 53.27 ± 8.27%, comparable to Trolox (45.74 ± 4.16%) in terms of antioxidant potential.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a diverse botanical family that comprises characteristic genera, including, but not limited to, Syzygium, Eucalyptus, Myricaria, Melaleuca, Eugenia, Myrtus, and Pisidium [14][15][16][17]. It has an economic potential value due to its pleasant sensory properties and bioactive constituents, and it is considered as a continuous source of antioxidant agents [18].…”
Section: Introductionmentioning
confidence: 99%